The Effect of Investment in The Banyuwangi Economy - M. Azizul Khakim (CV. Ulil Albab Corp, 2023)
Banyuwangi is the largest area in East Java. With natural wealth and tourism potential and the agricultural sector is getting better. So many investors have started to invest in Banyuwangi Regency. Likewise, people are starting to be interested in the world of investment, both in the capital market sector and the traditional investment sector. These reasons motivated researchers to continue their research related to the effect of investment in Banyuwangi Regency. This is in line with the high interest in investment, so there are also cases of civil and criminal crimes related to investment. All of these cases can occur because of the minimal level of public knowledge about investment and all its derivatives. Therefore, in addition to studying the influence of investment on the economy, this article also adds insight to the readers so that the level of crime and fraud under underinvestment can be suppressed.